A unified theory of dielectrophoresis and travelling wave dielectrophoresis - Parkash O.; Kumar D.; Prasad C.D. (My University, 2025)
Direct current resistivity and the Seebeck coefficient (alpha) have been measured in the temperature range 300-800 K for compositions x<or=0.40 in the Sr1-xLaxTi1-xCoxO3system. Alternating current conductivity has been measured as a function of frequency and temperature. Positive values of alpha over the entire range of measurement show that holes are the majority charge carriers. Alternating current conductivity shows that conduction occurs due to hopping of charge carriers among localized sites. © 1994 IOP Publishing Ltd.